Enhancing Transit Hotel Experiences: A Comparative Study of Interior Facility Requirements in Indonesian Transportation Hubs - Firmansyah Rangga; Nandaffa Azkia; Nangkula Utaberta; Nazlina Shaari; Sumarni Ismail (Journal of Architectural Research and Design Studies, 2024)
Short-term accommodations created to meet the needs of passengers in transit are known as transit hotels. The purpose of this study is to examine the necessary interior facilities for Indonesian transit hotels, with a focus on supporting and priority facilities. Three transit hotels situated in airports, train stations, and rest places along highways were the subject of semi-structured interviews and observations as part of a qualitative descriptive method. Qualitative analysis was performed on the gathered data, which included data reduction, data presentation, and conclusion drawing. The results show that depending on the location and length of the trip, different facilities are needed in transit hotels. All transit hotels must have priority facilities such as lobbies, reception areas, waiting lounges, and beds. On the other hand, supplementary facilities such as restaurants, fitness centres, prayer rooms, smoking areas, meeting spaces, locker rentals, and spas can be customized to fulfil the demands of users. In the end, this study offers helpful recommendations for the successful and efficient design of transit facilities for hotels, improving the transit experience for visitors to Indonesia. Keywords: interior design; priority facilities; supporting facilities; transit hotel